Cytokine Storm in the Novel Coronavirus Infection and Methods of its Correction - A. V. Ershov; V. D. Surova; V. T. Dolgikh; T. I. Dolgikh (Антибиотики и Химиотерапия, 2021)
The aim of the study was to identify the role of cytokine storm in COVID-19, that emerged at the end of 2019, based on the analysis of 80 publications, including 17.4% Russian and 82.6% foreign publications for 2014–2020 with an average impact factor of 11.94 and a maximum of 74.699. This review includes an in-depth discussion of the possible causes and pathogenetic factors of cytokine storm syndrome development caused by COVID-19. The results of research on the use of various principles of cytokine storm correction are provided. It has been established that lung damage and the development of a fatal outcome are caused not by the virus itself, but by the hyperreaction of the body's immune system. The leading role in this process belongs to the cytokine storm, including the action of IL-6.